1980
DOI: 10.1111/j.1755-3768.1980.tb05709.x
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrasonographic Study of Diabetic Vitreo‐retinal Disease With Low Visual Acuity

Abstract: Ninety-three diabetics (168 eyes) with opaque ocular media and low visual acuity (range amaurosis to 0.1) were examined by ultrasonography (A- and B-scan) using a Coleman Ophthalmoscan 100. Dense vitreous membranes were found in 112 (67%) eyes, 100 (60%) of which showed posterior membranes. Preretinal or prepapillary proliferations (extraretinal stalks) were demonstrated in 71 (42%) eyes. Fifty-four (32%) eyes had retinal detachments (40 localized, 14 total). These were present in 10 (50%) of the 20 amaurotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Jamil Ahmed et al (18) (2009) conducted a study 73 eyes of 68 patients with vitreous opacities and concluded that B-scan was very useful in detection and evaluation of vitreo-retinal pathologies Jemeld B et al (19) (1980) examined 93 diabetics (168 eyes) with opaque ocular media and low visual acuity by ultrasonography. The ultrasonic accuracy was checked in 49 eyes at vitrectomy.…”
Section: Comparison With Other Studies (Table 3)mentioning
confidence: 99%
“…Jamil Ahmed et al (18) (2009) conducted a study 73 eyes of 68 patients with vitreous opacities and concluded that B-scan was very useful in detection and evaluation of vitreo-retinal pathologies Jemeld B et al (19) (1980) examined 93 diabetics (168 eyes) with opaque ocular media and low visual acuity by ultrasonography. The ultrasonic accuracy was checked in 49 eyes at vitrectomy.…”
Section: Comparison With Other Studies (Table 3)mentioning
confidence: 99%
“…Em todos os casos, a cirurgia foi contra-indicada no olho com DR e foi realizada no olho contralateral. Em estudo realizado com 93 pacientes humanos diabéticos (168 olhos), Jerneld et al (1980) diagnosticaram, ultra-sonograficamente, DR em 32% dos olhos. Neste mesmo trabalho, determinou-se que a acurácia do ultra-som no diagnóstico de DR foi de apenas 78%.…”
Section: Discus Discus Discus Discus Discussão São São São Sãounclassified
“…Jemeld B et al, found US to be 78 % accurate whereas Rabinowitz R et al, found US to be 100 % accurate in diagnosing RD. 6,7 Posterior Vitreous Detachment and Vitreous Floaters: All 5 cases of Vitreous Detachment and 3cases of VF were correctly diagnosed by ultrasound. Rashmi et al found PHPV to be 100% specific and sensitive on usg.…”
mentioning
confidence: 95%